Lesser White-Fronted Goose Anser erythropus: good news about the breeding population in west Chukotka, Russia - Solovieva, Diana; Vartanyan, Sergey (Wildfowl, 2013)
A total of 243 Lesser White-fronted Geese Anser erythropus were counted along the Rauchua River and its main tributaries, the Konevaam and Ngagleyngyvaam Rivers, in July–August 2010. Average size of flocks that included broods was 27.5 individuals (s.d. = 10.7, range = 10–40, n = 8). Mean brood size was 3.57 goslings (s.d. = 1.22, range = 2–6, n = 14). Gosling age varied from 4 to 6.5 weeks. Of the Lesser Whitefronted Geese seen on the Rauchua River, 65% were young birds and 32.5% were brood-rearing (breeding) adults, whilst just 2.5% were non-breeders. We estimated that 500–600 pairs of Lesser White-fronted Geese bred in the Rauchua Basin in spring 2010, a dramatic increase from none present in 1983. This could indicate a local increase in response to human emigration from the catchment or a more general increase in the Eastern Population of the Lesser White-fronted Goose.